Weaving Archives. Riusare, reinventare e riprogettare i dati tessili - Margherita Tufarelli; Paolo Franzo (ZoneModa Journal)
With the spread of new technologies capable of shaping phygital spaces, where physical and digital reality intersect, great attention has been paid to business archives, their design, digitisation and reactivation. There are many relevant cases on the digitisation and reactivation of historical fashion archives, however, there are fewer experiments concerning textile archives, despite the crucial importance of the textile sector, particularly in Italy. The contribution analyzes the case study Prato Phygital, a project concluded in 2023 that saw the collaboration of universities, public institutions, museums and enterprises engaged in the elaboration of transmedia digital content from the materials of the business archives of the textile company Marini and the archives of the Museo del Tessuto in Prato. The project envisaged three main phases of implementation: (1) the elaboration of a digitisation procedure which, through the creation of a digital twin, would make it possible to reconstruct the fundamental characteristics of the selected textile materials, so as to convey their qualities on a digital support; (2) the use of the models obtained for the design of transmedia content; (3) the adaptation of this content to the development of audiovisual products, such as short films, films and animation, aimed at textile education. The textile archive thus becomes a generator of data, which is transformed into a new material for fashion.